Catalogue of Diptera of Colombia: an introduction - Wolff, Marta; Nihei, Silvio S.; Carvalho, Claudio J. B. De (Zootaxa, 2016)
Colombia has an imposing natural wealth due to its topography has many unique characteristics as a consequence of having Caribbean and Pacific shores, as well as sharing part of the Amazon basin and northern Andes mountains. Thus, many natural and biological features are due to the convergence of three biogeographical regions: Pacific, Andes and Amazonia. The Andean uplift created a complex mosaic of mountains and isolated valleys, including eleven biogeographical provinces (Morrone 2006). The Andes dominate the Colombian topography and cross the country south to north. There are three mountain ranges (Western, Central, and Eastern) with a maximum elevation of 5,775 m, and an average elevation of 2,000 m. The Magdalena and Cauca River valleys separate these ranges, that along with the Putumayo and Caquetá Rivers, the Catatumbo watershed, the Darién, Pique Hill, the Orinoquia Region (with its savannas), the Amazon region (with tropical rainforests), and some lower mountain ranges (Macarena and Chiribiquete), have generated the conditions for very high levels of endemism. This variety of conditions has resulted in an extremely diverse plant and animal biota, and in which 48% of the nation remains unexplored.